2016
DOI: 10.21873/anticanres.11092
|View full text |Cite
|
Sign up to set email alerts
|

The Significant Role of Cyclin D1 in the Synergistic Growth-inhibitory Effect of Combined Therapy of Vandetanib with 5-Fluorouracil for Gastric Cancer

Abstract: Abstract. Conclusion: The synergistic effect of vandetanib with 5-FU is related to vandetanib-induced reduction of TYMS via down-regulation of cyclin D1. Hyperexpression of cyclin D1 might be a biomarker of the synergistic effect.Gastric cancer is one of the most common malignant diseases worldwide, especially in the Asian countries (1). Although the expansion of multidisciplinary care, including advances in chemotherapeutic agents and surgical techniques, has progressed, gastric cancer is still a lifethrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Gastric cancer is one of the most common malignant diseases and the second leading cause of cancer-related deaths worldwide, especially in the Asian countries [ 1 ]. Despite great advances in surgical techniques and chemotherapeutic agents for gastric cancer, the 5-year-survival rate in patients is still unsatisfactory due to its metastasis and chemoresistance [ 2 , 3 ]. Therefore, it is indispensable to identify potential novel chemotherapy targets and understand their molecular mechanisms for improving the prognosis of gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer is one of the most common malignant diseases and the second leading cause of cancer-related deaths worldwide, especially in the Asian countries [ 1 ]. Despite great advances in surgical techniques and chemotherapeutic agents for gastric cancer, the 5-year-survival rate in patients is still unsatisfactory due to its metastasis and chemoresistance [ 2 , 3 ]. Therefore, it is indispensable to identify potential novel chemotherapy targets and understand their molecular mechanisms for improving the prognosis of gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…GC is a serious threat to humans because of its high incidence and mortality 2 , and China got the highest incidence of GC 3 . Despite great advances made in surgical techniques and chemotherapeutic agents, the 5-year survival rate of patients with GC is still dissatisfaction due to lack of early diagnosis and chemo-resistance 4 , 5 . Therefore, new and safe strategies to overcome chemotherapeutic resistance and minimize side effects are under exploration.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, for further quantitative analysis the variation of blood group B antibody concentration, the mouse monoclonal to anti-blood group B antibody in reagent was detected as Eppler A et al [ 36 ] and Yawata K et al [ 37 ] reported with some modification. As a result, the protein with a molecular weight about 181.7 kDa was identified as mouse anti-human blood group B antibody with concentration 0.57 mg/ml in the reagent (Fig.…”
Section: Discussionmentioning
confidence: 99%